An Indigenous Reading of Ella Cara Deloria’s Waterlily - Khadka, Kul Bahadur (The Saraswati Review, 2024)
Ella Cara Deloria’s novel “Waterlily” delves into the traditional Sioux society in America. Waterlily, the title character, is a hope for her mother Blue Bird. Blue Bird and Waterlily meet with lots of vicissitudes in their lives in the camp circles. Their family members and social relatives establish good ties and affinities with them. They sadden in their sorrows and rejoice in their smiles. This research, through an Indigenous perspective, analyzes the thematic patterns inherent in the novel and their significance for exploring ancestry and identity. The aim of the research is to show how traditions and cultures connect generations. The ideas developed by Linda Tuhiwai Smith from New Zealand and Daniel Heath Justice from America have been employed to analyze the novel. To enhance the study, Deloria’s “Waterlily” and various materials by Indigenous/Non-Indigenous writers and critics have been consulted. The novel inculcates the Indigenous ethos which includes values, symbols and respects for cultures and traditions essential for good human behaviors. Kinship, a principal ethos of Indigenous literatures, is the most important theme in the novel. It is kinship that trains humans to be human. The findings of the research come out that “Waterlily” as a decolonizing novel opens up the ancestral, cultural symbols and values; bridges the present people with their ancestors and coming generations, and helps marginalized people heal and go ahead with zeal.